2019
DOI: 10.1017/jfm.2019.550
|View full text |Cite
|
Sign up to set email alerts
|

Improved scaling laws for the shock-induced dispersal of a dense particle curtain

Abstract: Experiments were performed within Sandia National Labs’ Multiphase Shock Tube to measure and quantify the shock-induced dispersal of a shock/dense particle curtain interaction. Following interaction with a planar travelling shock wave, schlieren imaging at 75 kHz was used to track the upstream and downstream edges of the curtain. Data were obtained for two particle diameter ranges ($d_{p}=106{-}125$, $300{-}355~\unicode[STIX]{x03BC}\text{m}$) across Mach numbers ranging from 1.24 to 2.02. Using these data, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…0575, is large, indicating the particle motion is negligible over the simulation duration considered (t < 3). In addition, a recent experimental study suggests that the particle phase does not begin to spread until times corresponding to our non-dimensional time of t 10 [14]. Here, t = 0 corresponds to the instant the shock interacts with the leading edge of the particle phase.…”
Section: Simulation Configurationmentioning
confidence: 84%
See 2 more Smart Citations
“…0575, is large, indicating the particle motion is negligible over the simulation duration considered (t < 3). In addition, a recent experimental study suggests that the particle phase does not begin to spread until times corresponding to our non-dimensional time of t 10 [14]. Here, t = 0 corresponds to the instant the shock interacts with the leading edge of the particle phase.…”
Section: Simulation Configurationmentioning
confidence: 84%
“…In summary, the unclosed terms can be grouped into residual stresses R u in Eqs. (14) and (33), R µ in Eq. (15), R T u , R uu , and R τ u in Eq.…”
Section: A Summary Of Unclosed Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…The slope of the u p ( x ) profile at t B is reduced in case 6-120-50-0 since the rarefaction effect is partially offset by the more diffusive pressure field, which imposes countering pressure gradient forces throughout the column. At late time t C , the u p ( x ) profiles for both cases display a plateau, indicating a collective mobilization of particles (DeMauro et al 2019). The pressure profiles P ( x ) at t C vary little from those at t B .…”
Section: Resultsmentioning
confidence: 99%
“…Modelling granular materials as an isotropic elastic non-hardening Drucker–Prager solid, Kandan et al (2017) recognized that the instability criterion of the SDGI is equivalent to the Drucker–Prager yield criterion. However, the continuum approximation of granular materials is called into question due to the transient and non-equilibrium coupling between the interstitial gas phase and the particle skeleton in this scenario (Ben-Dor et al 1997; Britan, Shapiro & Ben-Dor 2007; DeMauro et al 2019). Previous studies revealed a complex wave spectrum inside a granular medium impinged head-on by an incident shock wave (Ben-Dor et al 1997; Britan et al 2007; Mo et al 2018, 2019; Koneru et al 2020).…”
Section: Introductionmentioning
confidence: 99%